The Existence and Social Functions of Sabeni Jawara from Tanah Abang in Contemporary Betawi Society - Velayati Khairiah Akbar; Yasir Mubarok (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
Amid the pressures of globalization and the growing dominance of transnational popular culture in Jakarta, the continuity of local oral traditions has become increasingly contested. This study investigates the existence and social functions of Betawi folklore through an analysis of Sabeni Jawara from Tanah Abang. Employing a qualitative descriptive design grounded in ethnolinguistics and dialogical ethnography, data were collected through field observations, in-depth interviews with Betawi cultural figures, and documentary analysis of folklore texts and related cultural sources. The findings reveal that Betawi folklore remains socially relevant not because it survives solely as an oral narrative, but because it has been institutionalized and recontextualized within contemporary cultural domains, including the Jakarta Local Culture and Environment Education curriculum (PLBJ), Lenong performances, and the Palang Pintu tradition. Functionally, the story of Sabeni Jawara operates as a vehicle for transmitting religious and moral values, fostering character education, and sustaining performative entertainment rooted in Betawi cultural aesthetics. More importantly, the study demonstrates that folklore functions as a dynamic mechanism for reproducing cultural identity, social memory, and collective values within a rapidly changing metropolitan environment. These findings contribute to folklore studies by showing how traditional narratives endure through processes of institutionalization, cultural performance, and identity reproduction, thereby positioning folklore not as a relic of the past but as an adaptive system of local knowledge that supports cultural sustainability in contemporary urban society.